Etika Profesional dalam Pelaksanaan Asesmen Psikologis di Konteks Bimbingan dan Konseling - Adelia Putri Nawindi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Ethics play an important role in the Psychological Assessment process in the realm of Guidance and Counseling, especially in maintaining the rights and welfare of clients. This article highlights two main ethical aspects, namely protecting the confidentiality of assessment results and efforts to maintain objectivity in its implementation. This study uses a literature study approach with a descriptive-qualitative analysis method. Information was collected from various scientific references such as books, journals, and professional guidelines, then analyzed to formulate relevant ethical principles and strategies for implementing them in assessment practice. The findings show that maintaining confidentiality requires a clear understanding of client rights, information boundaries, and secure data management procedures. Meanwhile, obstacles to maintaining objectivity can be overcome through increased competence, utilization of reliable assessment tools, and supervision support. The results of this study are expected to be a reference for counselors in implementing assessments ethically and professionally.